Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Menabung Pada Bank BRI Cabang Praya Lombok Tengah - Lalu Ardhi Kusuma (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2021)
This research aims to find and find out the factors that affect customers saving at Bank BRI Praya Branch, these factors include Products, Interest Rates, Places, Promotions, Processes, physical, employees and services. This type of research is descriptive research at Bank BRI Praya Branch, Jalan Gajah Mada No. 128 Praya Central Lombok. This research method is a sample survey, determining respondents using Simple Random Sampling. The analysis model used is qualitative using the Likert scale and quantitative using table anlisa and factor analysis. Based on the calculation of factor analysis results, six variables affect customer saving decisions, including Product Variables, Places, Processes, Physical, Employees, and Services. The six variables form the two factors that most affect the arena has an eigenvalue of more than 1.0 and loading factors above 0.4. Factor 1 has an eigenvalue of 1,914, and factor 2 has an eigenvalue of 1,587. The other two variables do not participate in the influence, namely for variable interest rates and promotions. The interest rate does not enter into because it has an MSA of less than 0.5. At the same time, the advertisement does not affect it because it has a loading factor of less than 0.4. Therefore, Bank BRI Praya Branch must pay attention to factors that influence customers by improving their quality and improving variables that do not affect to attract people to save more optimally in the future